KNOWLEDGE, ATTITUDE AND BEHAVIOR OF MIDWIVES AND NURSES WORKING IN PRIMARY HEALTH SERVICES ON BREAST CANCER EARLY DIAGNOSIS PRACTICES - Uncu, Fatos; Bilgin, Nevzat (Aves, 2011)
Purpose: Aim of this study was to determine knowledge, attitude and behavior of the midwives and nurses working in primary health services on breast cancer early diagnosis practices. Patients and Methods: The study charges 400 midwives and nurses who are working in 25 health centers located in the city center of Malatya. in this Cross-sectional and descriptive study the whole universe is included. Results: The average age of the midwife and nurses who attended to the survey (subjects), was 35.8 years for midwives and was 34.1 years for nurses. The education level of the participants varies as; 51.7 % (n=187) health professional high school, 39.8 % (n=144) health school (high school) and 8.5 % (n=31) bachelor degrees. Performance rate of breast self examination (BSE) rate was 56.1 % (n=203) among the participants, 15.5 % (n=56) of the midwives and nurses applies BSE regularly, but 40.6 % (n=147) irregularly, while 43.9 % (n=159) does not apply at all. Approximately fourty-eight of participants had adequate knowledge about BSE technique and 10.2 % (n=37) had no knowledge at all. Among participants 40.3 % (n=146) had clinical breast examination. Only, 25.4 % (n=92) of the participants had a mammogram exam but, 74.6 % (n=270) did not. These three methods which are important for early diagnosis of breast cancer were used together only 13.8 % (n=50) of the midwives and nurses participating of the research. Conclusion: In the results of study, it is suggested that midwives and nurses should be support by education their deficiencies about breast cancer early diagnosis practices.
Keywords: midwife; nurse; breast self examination; clinical breast exam; mammography